A chromosome‐level genome assembly of Paracymoriza distinctalis (Lepidoptera: Crambidae: Acentropinae). Issue 2 (16th March 2022) - Chen, Xiaoning; Zhu, Wenbo; Wang, Biao; Wang, Yuqi; You, Ping
Abstract: Paracymoriza distinctalis is a semiaquatic lepidopteran insect, which is of great value for studying the differentiation of the Pyraloidea superfamily. However, the understanding of heredity, evolution, and functional genomics of P. distinctalis are limited by few genome‐wide resources. Here, we applied PacBio sequencing and the chromosome capture technique to assemble the first P. distinctalis genome from a single female individual. The genome size is 1.2 Gb with 32 chromosomes and the N50 is 38.91 Mb. Approximately 576.37 Mb, accounting for 48.93% of the genome, was identified as repeats. The genome comprises 39, 003 protein‐coding genes, 66.56% of which were functionally annotated. Comparative genomics analysis suggested that the common ancestor of P. distinctalis and Chilo suppressalis lived ~83.5 million years ago. This chromosome‐level genome assembly work is not only conducive to the understanding of P. distinctalis, but also may promote the study of the genomes of other lepidopteran species. Abstract : We sequenced and present the first chromosome‐level genome for Paracymoriza distinctalis (Lepidoptera: Crambidae: Acentropinae). The P. distinctalis genome provides a valuable resource for important gene mining and deeper comparative genomics analyses in the future. Genome sequences would enable us to further explore the divergence of the Acentropinae lineage. It is thus essential to obtain high‐quality genome resources to guide the development of these species in applications with respect to agriculture, environmental conservation.